KARAKTERISTIK PEKERJAAN, DUKUNGAN SOSIAL DAN TINGKAT BURN-OUT PADA NON HUMAN SERVICE CORPORATION - Fery Farhati; Haryanto F Rosyid (Jurnal Psikologi, 1996)
The aims of this study are (1) to investigate the relationship betwewn job characterictics and burn-out, and social support and burn-out. (2) is to elaborate the role of both variables i.e. job characteristics and aocial support on manifestation of perceived burn out. Subjects of the study were 63 employees of non human service corporate in Jakarta.